IoT-Based Fire Automatic Surveillance System with Sprinkler Control Systems - Lehon, Mohd Faizul; Mohd Zin, Rosnah (Evolution in Electrical and Electronic Engineering, 2026)
The principal objective of this project is to develop an Internet of Things (IoT) based fire automatic surveillance system with sprinkler control for early fire detection and suppression in indoor environments. To limit damage and improve response times, the system is designed to continuously monitor fire-related factors, including temperature, smoke concentration, and flame presence. Conventional fire detection systems often rely on single sensors and human intervention, which can lead to greater danger and delayed response. The suggested device combines an ESP8266 NodeMCU microcontroller with an IR flame sensor, MQ-2 smoke sensor, and BMP280 temperature sensor to get around this limit. When set threshold values are exceeded, the system is designed to automatically activate a buzzer alarm and a spray of water. The system also uses Wi-Fi connectivity and the Blynk IoT platform for mobile notifications and real-time monitoring. The system can identify fire conditions with an average response time of 7.13 seconds and a cumulative detection accuracy of 66.91%, according to experimental testing. This intelligent fire monitoring system provides a dependable, affordable, and useful way to improve fire safety in homes, workplaces, and laboratories.